Rancang bangun media pembelajaran berbasis flash di slb koto agung: Flash-Based Interactive Learning Media Design at SLB Koto Agung - putra, khaironi; Revita, Elinda; Asril, Asril (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2023)
Flash-Based Interactive Learning Media Design at SLB Koto Agung aims to provide skills in the design of attractive interactive learning media in an easy way. By mastering interactive learning media by teachers, it is hoped that it can trigger students' interest to be more enthusiastic in participating in lessons, and in the end it will improve the overall quality of learning. In this study, the application of learning at SLB Koto Agung which has been done manually or not yet computerized which allows there are still many shortcomings in the teaching and learning process. The research method used is observation and interviews. The result of this research is the design of interactive learning media that has the ability to provide convenience for teachers in delivering material to students.